Uji Perkecambahan Buah Jati Muna dan Jati Malabar Muna - Arum Sekar Wulandari (Institut Pertanian Bogor, 2007)
Germination of teak is often poor. The study on fruits and seeds germination of Java teak, Muna teak, and Malabar Muna teak was conducted in a series of laboratory and greenhouse experiment. Teak fruits have saveral types of dormancy. So, fruits need pretreatment before they were planted. A recommended pretreatment of teak fruits is to soak the fruits during the night and dry them in the sun during the day.Keyword: teak, Tectoca grandis, fruit germination, seed germination